Multidimensional Comparison of Lightweight Steel and Reinforced Concrete Structures: A Case Study - Celik, Tolga; Kamali, Saeed (Univ Osijek, Tech Fac, 2018)
Lightweight steel construction has some undeniable advantages over concrete construction; however, reinforced concrete structures are used ubiquitously in Mediterranean countries and therefore most of the scientific studies have been focused on the reinforced concrete structures. One of the main reasons for not using the lightweight steel construction widely is lack on knowhow about this method. This study is aimed at raising the knowledge about the technical features of cold-formed steel members as well as advantages of lightweight steel structure in comparison with reinforced concrete. To fulfil this aim, a case study was conducted to compare lightweight steel structure with reinforced concrete structure in different points of view in detail. From the case study, it is found out that the building total covered area and mass designed by reinforced concrete structure are 2.6% larger and 9 times greater than the lightweight steel structure respectively. It was also concluded that the total cost ( indirect and direct) and construction duration for the reinforced concrete structural frame are approximately 17.7% and 70.9% respectively higher than constructing the lightweight steel structural frame.
Keywords: life cycle cost; lightweight steel construction; reinforced concrete construction; sustainability